2022
DOI: 10.1371/journal.pone.0262142
|View full text |Cite
|
Sign up to set email alerts
|

Communities’ perceptions towards cervical cancer and its screening in Wolaita zone, southern Ethiopia: A qualitative study

Abstract: Background Cervical cancer is a malignant neoplasm from cells originating in the cervix uteri. Any woman who is sexually active is at risk of getting HPV. Women in sub-Saharan Africa region have higher chance of developing the disease. There are nearly 26 million Ethiopian women who are over the age of 15 and believed to be at risk of getting HPV. Regrettably, Ethiopian women typically present for cervical cancer care at a late stage in the disease, where treatment is most ineffective. Objectives To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…At present, there are two major bottlenecks in treatment: one is the immature early diagnosis method, and the other is the low survival rate of advanced cancer treatment. Therefore, it is necessary to identify the molecular mechanisms of occurrence and progression of CC as well as the therapeutic targets [ 15 ]. Starting from molecular and protein expression and function, this study found through various experiments that ZEB1 could promote the growth and metastasis of CC cells via modulating PD-1/PD-L1, which is of great clinical implications for the early diagnosis of CC and identifying new therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are two major bottlenecks in treatment: one is the immature early diagnosis method, and the other is the low survival rate of advanced cancer treatment. Therefore, it is necessary to identify the molecular mechanisms of occurrence and progression of CC as well as the therapeutic targets [ 15 ]. Starting from molecular and protein expression and function, this study found through various experiments that ZEB1 could promote the growth and metastasis of CC cells via modulating PD-1/PD-L1, which is of great clinical implications for the early diagnosis of CC and identifying new therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological burden experienced by male partners during the disclosure of cervical cancer diagnostic results could be explained by limited awareness, negative attitudes, and perceptions of cancer in society. In many societies, cancer is perceived as a debilitating and life‐threatening condition, regardless of the type or stage at which it is revealed 35‐37 . This study also revealed that most of the individual participants and their societies believed that cervical cancer was incurable and meant an immense death.…”
Section: Discussionmentioning
confidence: 67%
“…Negative attitudes towards cervical cancer in society can fuel myths and misconceptions, which in turn perpetuate stigma towards women suffering from cervical cancer and their families, and this may eventually hamper the effectiveness of cervical cancer prevention strategies 42,43 . Inline, a community study conducted in Ethiopia found that the majority of the participants in the study were not aware of cervical cancer, its risk factors or preventive measures 44 . The study provides consistent evidence that had been reported previously regarding the significance of addressing society's attitudes and providing correct information about cervical cancer 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, little attention has been paid to examining the impact of culture, socioeconomic status, and religious beliefs on public awareness of cancer [28]. So far, few studies have been undertaken to examine public awareness of specific cancer types, such as cervical [29][30][31], breast [32][33][34], and colorectal cancers [35]. Moreover, more than 80% of cancer cases in Ethiopia are identified at an advanced stage, which is suggested to be due to a lack of public awareness of cancer signs and symptoms [28].…”
Section: Introductionmentioning
confidence: 99%